Peran Pendidikan Agama Kristen dalam Memerangi Radikalisme dan Ekstremisme: Menumbuhkan Cinta, Perdamaian, dan Rasa Hormat - Jefrit Johanis Messakh; Esti Regina Boiliu (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2023)
The spread of radicalism and extremism has become a global concern in recent decades. Issues regarding radicalism and extremism continue to develop in a flurry of problems. This requires the active role of Christian Religious Education to be carried out in a structured manner in order to be able to overcome this challenge by cultivating love, peace and respect. The purpose of this study is to describe the role of Christian Religious Education in fighting radicalism and extremism. The method used in this research is literature study. The result of this research is that Christian religious education can be a powerful force in fighting radicalism and extremism by instilling universal values such as love, peace and respect for fellow human beings. Christian Religious Education also plays a role in developing a deep understanding of Christian teachings which include values such as love for others, forgiveness, understanding, and tolerance. Christian Religious Education must build intercultural skills, and integrate social issues in the Christian Religious Education curriculum.